Determination of water column characteristics in coastal environments using remote sensing. - Hick, Peter T. (Curtin University, 1997)
This thesis illustrates the specific aspects that influence or limit the application of remotely-sensed data for information retrieval from coastal marine, estuarine and riverine environments. The thesis is drawn principally from ten separate studies and is divided into discrete sections, or experiments, that provide an understanding of the fundamental aspects of the effects of the atmosphere, water surface, water column and bottom on sensor-received reflected signal.The results show the importance of precise calculation of acquisition parameters and the absolute importance of relevant reference data. Most instrumentation for remote sensing at visible wavelengths has been developed for terrestrial applications where signal is rarely limiting and target features are relatively static. For in-water applications, where signal is small and noise can be large, the features to be sensed may be temporally dynamic and obscured.However, the work presented also shows the great benefit and spatial cost-effectiveness that can be obtained if the spectral and temporal specification is adequately considered. The prime motivation for such applications usually comes from the requirement to detect and quantify water column characteristics, such as phytoplankton forming as algal blooms, and bottom stratigraphic condition, such as benthic habitat mapping for fishery or conservation purposes.